Relationship Between Mother's Education Level and Incidence of Stunting in Children Aged 6-59 Months: Hubungan Tingkat Pendidikan Ibu dengan Kejadian Stunting Pada Anak Usia 6-59 Bulan - Heni Anggraini (Indonesian Journal of Administration and Health Research (IJAHR), 2024)
Background: One of the main focus of nutrition problems is stunting in children under five years old. Stunting is a condition of growth failure in children under five years old. There are 100 districts / cities in Indonesia where the incidence of stunting is the highest and is a priority for the government to handle. And 3 of them are in Lampung Province, namely South Lampung 43.01%, Lampung 43.17% and Central Lampung 52.68%. Objective: To determine the relationship between maternal education level and family income with the incidence of stunting in children aged 6-59 months. Methods: This study was an observational analytic with a cross sectional approach. The sample of this study was 75 children aged 6-59 months obtained from purposive sampling calculation. Data analysis using chi square test. Results: There is a relationship between maternal education level and stunting with the results, namely the OR value of 3.313 (CI: 1.878 - 5.848) and the p value of 0.000 or p value <0.05.  The test results obtained a p value of 0.000 <0.05.  Conclusion: Low maternal education has a 3.313 times higher risk of stunting (<-2SD) compared to mothers with higher education. Higher maternal education is generally associated with better knowledge on nutrition, access to health services, and adequate parenting. Therefore, exploring the relationship between maternal education and the incidence of stunting may assist in the development of more effective public health policies